Status Epilepticus Due to Severe HHV-6 Encephalitis in an Allogeneic Stem Cell Transplant Recipient - Poorvi Chordia; Pranatharthi H Chandrasekar (Mediterranean Journal of Hematology and Infectious Diseases)
Reactivation of human herpes virus-6 (HHV-6) after stem cell transplantation occurs frequently. It is associated with clinical manifestations varying from nonspecific symptoms such as fevers or rash, to severe life threatening complications including post-transplantation limbic encephalitis. We report a case of severe HHV-6 encephalitis with viremia in an allogeneic peripheral stem cell transplant recipient who presented with status epilepticus unresponsive to antiepileptic therapy.  With intravenous ganciclovir and supportive care, the patient’s condition improved. Awareness of HHV-6 infection in stem cell transplant recipients may help with early diagnosis and improved outcome.